Immobilization of Cutinase from Fussarium oxysporum into Sea Sand Matrix for Catalytic Degradation of Polyethylene Terephthalate (PET) - Prameswari, Tira P. K.; Sutrisno, Sutrisno; Roosdiana, Anna (Chemistry Department, The University of Brawijaya, 2024)
Cutinase is an enzyme that can be used as a catalyst in the hydrolysis reaction of polyethylene terephthalate (PET) waste into terephthalic acid and ethylene glycol. Generally, cutinase has low stability in its free form. Therefore, to increase cutinase stability, cutinase needs to be immobilized. In this study, cutinase was immobilized into a sea sand matrix by adsorption technique. The purpose of this study was to determine the optimum conditions of PET hydrolysis (pH, temperature, and incubation time), and to study the ability of immobilized cutinase for catalytic degradation of PET. The results show that immobilized cutinase has optimum conditions at pH 8, temperature of 50 Â°C, and incubation time of 24 hrs. Moreover, the immobilized cutinase can be used for up to three cycles with a residual activity percentage of 66.2% and an activity value of 23.224 nmol. g-1. min-1. The total enzyme activity of immobilized cutinase after being used in three cycles was 89.99 nmol. g-1. min-1 or 28.6% of its free enzyme activity.